Handbook of heterocyclic chemistry - Katritzky, Alan R. (Elsevier, 2010)
Heterocyclic compounds play a vital role in the metabolism of living cells. Their practical applications range from extensive clinical use to fields as diverse as agriculture, photography, biocide formulation and polymer science. Written by leading scholars and industry experts, the Handbook of Heterocyclic Chemistry contains more than 1500 clearly drawn structures and reactions. The highly systematic coverage given to the subject makes this one of the most authoritative single-volume accounts of modern heterocyclic chemistry available.
Previous edition: 2000.
Keywords: Heterocyclic chemistry.; elektronické knihy; electronic books